Haploidentical versus matched unrelated donor transplants using post-transplantation cyclophosphamide for lymphomas - Mussetti, Alberto; Kanate, Abraham S.; Wang, Tao; He, Meilun; Hamadani, Mehdi; Finel, Hervé; Boumendil, Ariane; Glass, Bertram; Castagna, Luca; Dominietto, Alida; McGuirk, Joseph; Blaise, Didier; et al. (Transplantation and cellular therapy, 2023)
When using post-transplantation cyclophosphamide (PTCy) graft-versus-host disease (GVHD) prophylaxis for lymphoma patients, it is currently unknown whether a matched unrelated donor (MUD) or a haploidentical related donor is preferable if both are available. In this study we wanted to test whether using a haploidentical donor has the same results of a MUD. A total of 2140 adults (34% Center for International Blood and Marrow Transplant Research, 66% European Society for Blood and Marrow Transplantation registry) aged ≥18 years who received their first haploidentical hematopoietic cell transplantation (haplo-HCT) or MUD-HCT (8/8 match at HLA-loci A, B, C, and DRB1) for lymphoma using PTCy-based GVHD prophylaxis from 2010 to 2019 were retrospectively analyzed. The majority of both MUD and haploidentical HCTs received reduced intensity/nonmyeloablative conditioning (74% and 77%, respectively) and used a peripheral blood stem cell graft (91% and 60%, respectively) and a 3-drug GVHD prophylaxis (PTCy + calcineurin inhibitor + MMF in 54% and 90%, respectively). Haploidentical HCT has less favorable results versus MUD cohort in terms of overall mortality (hazard ratio [HR= = 1.69; 95% confidence interval [CI], 1.30-2.27; P < .001), progression-free survival (HR=1.39; 95% CI, 1.10-1.79; P = .008), nonrelapse mortality (HR = 1.93; 95% CI, 1.21-3.07; P = .006), platelet engraftment (HR = 0.69; 95% CI, 0.59-0.80; P < .001), acute grade 2-4 GVHD incidence (HR = 1.65; 95% CI, 1.28-2.14; P < .001), and chronic GVHD (HR = 1.79; 95% CI, 1.30-2.48, P < .001). No significant differences were observed in terms of relapse and neutrophil engraftment. Adjusting for propensity score yielded similar results. Whenever MUD is available in a timely manner, it should be preferred over a haploidentical donor when using PTCy-based GVHD prophylaxis for patients with lymphoma.
Online verfügbar 25. Dezember 2022, Artikelversion 28. Februar 2023
Gesehen am 11.07.2023